PENGALAMAN SPIRITUALITAS DOA PASIEN HIV/AIDS DI RSUD SAWERIGADING PALOPO DENGAN PENDEKATAN TEORI CALISTA ROY - Sugiyanto; Emiliana Tarigan; Indriati Kusumaningsih (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2018)
When a person has been diagnosed with HIV/AIDS, he will experience changes in his life such as changes in behavior, social change, and psychological changes. These changes can be a mental pressure or psychological stressors for people with HIV/AIDS. Conditions like this, people with HIV / AIDS need a lot of support, one of which is the support of spirituality. Spirituality and praying aspects may not be separated from human life, either in health or unhealthy/ill condition. Closely, it is correlated with treatment process for patient with HIV/AIDS. The aim of research is to discovering spirituality and praying experience to patient with HIV/AIDS with the approach of the Calista Roy Nursing Theory. This research design is qualitative with phenomenology approach. Four participantshad participated in this research by telling his/her related with spirituality and praying experience. Data collection conducted using of indeepth interview and using aid tool of interview guide, field research/notes, and document study. The data analyze using both Collaizi (1978) and software of QSR Nvivo. This research result reveals seven (7) themes those are: (1) sorrow process of HIV/AIDS patient; (2) family support to HIV/AIDS patient; (3) HIV/AIDS value against sufferer; (4) method of approaching God (5) essence of praying for HIV/AIDS sufferer; (6) life wishing/acceptance, and (7) nursery service wish. This research recommend for further research related with gender variance, increasing of service quality of nursery holistically and spiritual aspect more specifically as well as to grow caring attitude to implement nursery to patient.